Curcumin Reduced H2O2- and G2385R-LRRK2-Induced Neurodegeneration - Zhang, Jinru; Li, Kai; Wang, Xiaobo; Smith, Amber M.; Ning, Bo; Liu, Zhaohui; Liu, Chunfeng; Ross, Christopher A.; Smith, Wanli W. (Frontiers in Aging Neuroscience, 2021)
Mutations in leucine-rich repeat kinase 2 gene (LRRK2) are the most frequent genetic factors contributing to Parkinson’s disease (PD). G2385R-LRRK2 in Chinese population increases the risk for PD susceptibility. However, the pathological role of G2385R-LRRK2 is not clear. In this study, we investigate the roles of G2385R-LRRK2 in neurodegeneration underlying PD pathogenesis using cell biology and pharmacology approaches. We demonstrated that expression of G2385R-LRRK2 induced neurotoxicity in human neuroblastoma SH-SY5Y and mouse primary neurons. G2385R-LRRK2 increased mitochondrial ROS, activates caspase-3/7, and increased PARP cleavage resulting in neurotoxicity. Treatment with curcumin (an antioxidant) significantly protected against G2385R-LRRK2-induced neurodegeneration by reducing mitochondrial ROS, caspase-3/7 activation and PARP cleavage. We also found that cellular environmental stressor, H2O2 significantly promotes both WT-LRRK2 and G2358R-LRRK2-induced neurotoxicity by increasing mitochondrial ROS, caspase-3/7 activation and PARP cleavage, while curcumin attenuated this combined neurotoxicity. These findings not only provide the novel understanding of G2385R roles in neurodegeneration and environment interaction, but also provide a pharmacological approach for intervention for G2385R-LRRK2-linked PD.